2021
DOI: 10.1038/s41598-021-83909-3
|View full text |Cite
|
Sign up to set email alerts
|

A target enrichment high throughput sequencing system for characterization of BLV whole genome sequence, integration sites, clonality and host SNP

Abstract: Bovine leukemia virus (BLV) is an oncogenic retrovirus which induces malignant lymphoma termed enzootic bovine leukosis (EBL) after a long incubation period. Insertion sites of the BLV proviral genome as well as the associations between disease progression and polymorphisms of the virus and host genome are not fully understood. To characterize the biological coherence between virus and host, we developed a DNA-capture-seq approach, in which DNA probes were used to efficiently enrich target sequence reads from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 43 publications
(70 reference statements)
4
22
2
1
Order By: Relevance
“…Evaluation of this method showed efficient enrichment of target sequence reads and integration of the BLV proviral genome in persistently infected FLK-BLV cells. Our visualization of sequences of paired-end reads mapped to the host genome in DNA from FLK-BLV cells showed a pattern similar to that reported in a previous publication [ 29 ]. Secondly, we found evidence for the first-time regarding two BLV integration sites in BLSC-KU1 and BLSC-KU17 cells using our newly developed proviral DNA-capture-seq.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Evaluation of this method showed efficient enrichment of target sequence reads and integration of the BLV proviral genome in persistently infected FLK-BLV cells. Our visualization of sequences of paired-end reads mapped to the host genome in DNA from FLK-BLV cells showed a pattern similar to that reported in a previous publication [ 29 ]. Secondly, we found evidence for the first-time regarding two BLV integration sites in BLSC-KU1 and BLSC-KU17 cells using our newly developed proviral DNA-capture-seq.…”
Section: Discussionsupporting
confidence: 84%
“…We analyzed the BLV integration sites in FLK-BLV cells. FLK-BLV cells have often been used as controls in studies related to BLV; previous studies have showed multiple copies of the BLV genome integrated into the genome of the FLK-BLV cells by either Southern blotting analysis [ 2 , 33 ] or target enrichment next-generation sequencing (NGS) [ 29 ]. The five biotinylated probes used in this study efficiently and specifically captured the BLV provirus and proviral–host chimeric DNA fragments in the DNA library of FLK-BLV cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Лимфома, индуцированная BVL, развивается в результате взаимодействия элементов генома вируса и продуктов генома хозяина в дополнение к BoLA-DRB3. Например, интеграция провируса BLV в районе генов хозяина, вовлекаемых в процесс онкогенеза, влияет на их экспрессию (52)(53)(54)(55). В ряде работ отмечается, что достаточно часто интеграция провируса BLV выявляется в районах локализации ретровирусов (56)(57)(58)(59)(60).…”
unclassified